2022
DOI: 10.1186/s40814-022-00970-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an MI-CBT ketogenic adherence program for older adults with mild cognitive impairment

Abstract: Background The National Institutes of Health Obesity-Related Behavioral Intervention Trials model for intervention development was used to establish the feasibility and proof of concept of a motivational ketogenic nutrition adherence program for older adults with mild cognitive impairment. Methods This was a single-arm, single-center feasibility trial. A comprehensive assessment protocol, including a clinical interview, neuropsychological testing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Another small trial showed the ketogenic diet improved a cognitive component of the Alzheimer’s disease Assessment scale over a 12-week intervention [ 37 ]. Finally, yet another small trial conducted by Sheffler et al included 9 older adults who were counseled to consume a ketogenic diet for 6 weeks, after which they observed significant improvement in cognitive performance [ 38 ]. Taken together, these small clinical trials support the ketogenic diet as a potential therapeutic strategy for mild cognitive impairment with aging.…”
Section: The Mindmentioning
confidence: 99%
“…Another small trial showed the ketogenic diet improved a cognitive component of the Alzheimer’s disease Assessment scale over a 12-week intervention [ 37 ]. Finally, yet another small trial conducted by Sheffler et al included 9 older adults who were counseled to consume a ketogenic diet for 6 weeks, after which they observed significant improvement in cognitive performance [ 38 ]. Taken together, these small clinical trials support the ketogenic diet as a potential therapeutic strategy for mild cognitive impairment with aging.…”
Section: The Mindmentioning
confidence: 99%
“…Further, ORBIT provides a pathway for refining and tailoring interventions to address community needs and improve scaling and dissemination of effective interventions. Using the ORBIT model, our team established the proof-of-concept for a community-focused MKN program that uses motivational interviewing strategies and behavior change techniques (MI-BCT) to enhance adherence [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…BCTs are often considered the ‘active ingredient’ in behavioral interventions that influence mechanisms of action [ 18 ]. Our team used the NIH ORBIT framework for developing behavioral interventions to address chronic conditions [ 16 ] and has previously established the proof-of-concept for this MKN adherence (MKNA) program [ 17 ].…”
Section: Introductionmentioning
confidence: 99%